ANALISIS MAKNA GERAK TARI RADAT APE NANG DITUMBOK KABUPATEN SAMBAS KALIMANTAN BARAT - Budiman Budiman; Ismunandar Ismunandar; Asfar Munir (Universitas Tanjungpura, 2019)
AbstractHaving lacked documentation to preserve information related to dance as part of the culture of the Malay in Sambas Regency has been the concern of the researcher. This study aims to analyze the meaning of movements and supporting elements used in the Radat dance titled Ape Nang Ditumbok and to document it into a video and written form. The method used in this study is descriptive analysis in the form of qualitative with the semiotic approach. The data were obtained through observation, interviews, and documentation from the local artists. The data were validated by extended observation and triangulation techniques (source triangulation). Radat dance Ape Nang Ditumbok is a group dance played by 12 women, accompanied by percussion instruments played by men. Ape Nang Ditumbok consists of 5 movements: swinging, pounding and winnowing rice, timang burung, nyiur melambai, and the movement showing sadness or happiness. The movements in this dance come from daily activities such as walking, working, movements representing animals and plants, and human expression. The Raddat dance Ape Nang Ditumbok originally functioned as entertainment in an event held in the royal palace Sambas and the wedding of the nobility. As it develops, the dance is also performed at public weddings, festivals, religious rituals, dance performances, and competitions. This traditional dance was created on the basis of a poem, and later the movements were created. Additionally, the Radat dance Ape Nang Ditumbok can be used as teaching material for teaching and learning theory and practice in the subjects of Cultural Arts and Skills. Keywords : Analysis, dance movement, Radat Dance Ape Nang Ditumbok